Human cytomegalovirus infection-induced lymphocytosis diagnosed by metagenomic next-generation sequencing: a case report and literature review - Zhang, Shaofan; Sun, Li; Wang, Liman; Liu, Yuwei; Tan, Gao; Liu, Tao; Yang, Wen; Liu, Xiaoli (Frontiers in Immunology, 2025)
BackgroundHuman cytomegalovirus (HCMV) exhibits a high prevalence and is a major threat to immunocompromised individuals. Conventional diagnostic modalities are increasingly struggling to meet evolving clinical needs. Metagenomic next-generation sequencing (mNGS) represents a valuable tool for expeditious microbial identification in diagnostically complex cases.Case presentationA 35-year-old man presented with fever, pharyngitis, fatigue, and marked lymphocytosis. No significant abnormalities were detected in imaging and routine tests, and conventional pathogen detection methods failed to identify any suspected pathogens. Targeted next-generation sequencing (tNGS) identified five pathogens: Staphylococcus aureus, Streptococcus mitis group, rhinovirus C, cytomegalovirus (CMV), and human herpesvirus-7. Clinical symptoms alleviated within 7 days of ganciclovir therapy initiation; however, lymphocytosis persisted. Subsequently, mNGS was performed, confirming HCMV infection and providing a definitive diagnosis. During follow-up, the patient’s symptoms had largely resolved.ConclusionSymptomatic HCMV infections primarily affect immunocompromised individuals, while persistent lymphocytosis associated with HCMV is uncommon. This case highlights the diagnostic and therapeutic utility of mNGS in HCMV infection, especially when conventional diagnostic methods are limited, pathogen abundance is low, and the patient is immunocompromised.